989 IS DIET QUALITY AS IMPORTANT AS DIET QUANTITY IN THE OLDER ADULT? MICRONUTRIENT DEFICIENCY, FRAILTY AND SARCOPENIA. (14th June 2022) - Jennings, C; Slee, A; Weekes, C E
Abstract: Introduction: Dietary research in older adults has focused on energy content, macronutrient composition and diet quantity. Dietary antioxidants can theoretically ameliorate oxidative stress, which is widely implicated in age-related degeneration. Additional vital micronutrients are magnesium, being a co-factor for antioxidant enzyme function, and potassium, given its role in nerve and muscle function, and fluid balance. This study sought to investigate diet quality, specifically micronutrient content, and independent nutritional risk factors for frailty and sarcopenia. Method: Secondary analysis of NUTRICOM 2015–2018 study participants (NIHR 19045)—exploring the impact of malnutrition on community-dwelling older adults—was conducted. Dietary intake was assessed using multiple-pass 24-hour dietary recall, nutrition risk status (NRS) using Guy's and St Thomas' NRS Tool, frailty using the 7-point Clinical Frailty Scale (CFS) and sarcopenia using EWGSOP2 handgrip strength cut-offs. Mann–Whitney U-Test assessed differences in dietary intake between malnutrition risk groups. Multivariable regression models, adjusting for age, gender, deprivation and comorbidities, established nutritional correlates of frailty and sarcopenia. Results: 142 participants; mean age 77.4(SD 8.4) years, 83(59%) female, mean BMI 26.05(SD 5.35). 79%–91% of older adults showed dietary deficiency in zinc, selenium, copper, magnesium and potassium. CFS increase was independently associated with NRS, and deficiency of potassium, copper and cumulative micronutrients, by 1.52, 1.19, 0.82 and 0.28 respectively (p < 0.05). Individuals with dietary zinc deficiency were 3.25 times more likely to have sarcopenia than individuals with sufficient zinc intake (95%CI: 1.04–10.16, p = 0.042). Conclusion: Routine nutrition risk screening (accounting for macronutrient intake) finds only about 5% of older adults to be at-risk of malnutrition, whilst assessment of dietary intake in this study suggests dietary micronutrient deficiency is very common and is associated with increased frailty. 24-hour recall only provides a snapshot of dietary intake; further studies should be conducted using method that measure habitual dietary intake e.g. 7-day dietary diary.